2017
DOI: 10.3390/ijms18071397
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bone Mineral Density Associated with Age in Male Rats Fed on Sunflower Oil Is Avoided by Virgin Olive Oil Intake or Coenzyme Q Supplementation

Abstract: The role of dietary fat unsaturation and the supplementation of coenzyme Q have been evaluated in relation to bone health. Male Wistar rats were maintained for 6 or 24 months on two diets varying in the fat source, namely virgin olive oil, rich in monounsaturated fatty acids, or sunflower oil, rich in n-6 polyunsaturated fatty acids. Both dietary fats were supplemented or not with coenzyme Q10 (CoQ10). Bone mineral density (BMD) was evaluated in the femur. Serum levels of osteocalcin, osteopontin, receptor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…In fact, the negative correlation found between oleic and urinary 15-F2t-isoprostane may suggest that a longer intervention would be able to exert a positive effect on reducing urinary 15-F2t-isoprostane concentrations. This is in agreement with other published preclinical [50] and clinical [51] studies.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the negative correlation found between oleic and urinary 15-F2t-isoprostane may suggest that a longer intervention would be able to exert a positive effect on reducing urinary 15-F2t-isoprostane concentrations. This is in agreement with other published preclinical [50] and clinical [51] studies.…”
Section: Discussionsupporting
confidence: 93%
“…These effects were observed when sunflower oil was administered in a proportion of 8% w / w in the diet, which is the double of current recommendations for rodents [172]. This is in concordance with other findings in different tissues and organs of old and young rats fed on similar diets [173,174,175,176,177,178,179,180,181,182,183,184]. Alternatively, it has been suggested that CoQ 10 supplementation does not truly extend life span, but that it could prevent life span shortening due to oxidative insults [161], as has been suggested by its effect in all aspects related to mitochondrial function, oxidative stress and antioxidant defenses both in animals and humans (Figure 2b).…”
Section: Dietary Supplementation Of Coq10 During Agingsupporting
confidence: 89%
“…On the other hand, the different oils used could modulate CoQ 10 absorption since fatty acids significantly help in the absorption of CoQ 10 via bile acid production [185,186]. In animals fed on similar CoQ-supplemented diets, plasma CoQ 10 concentration values were 39.24 ± 9.25 and 50.71 ± 5.22 μM when they received a diet based on virgin olive oil and sunflower oil, respectively [174]. Another study reported even lower values in those animals fed on a fish oil-based diet [182].…”
Section: Dietary Supplementation Of Coq10 During Agingmentioning
confidence: 99%
See 2 more Smart Citations